Continuation phase treatment outcomes for switching, combining, or augmenting strategies for treatment‐resistant major depressive disorder: A VAST‐D report. Issue 2 (22nd November 2020) - Zisook, Sidney; Johnson, Gary R.; Hicks, Paul; Chen, Peijun; Beresford, Thomas; Michalets, James P.; Rao, Sanjai; Thase, Michael E.; Wilcox, James; Sevilimedu, Varadan; Mohamed, Somaia
Abstract: Background: This secondary analysis of the VA Augmentation and Switching Treatments for Depression study compared the continuation phase treatment outcomes of three commonly used second‐step treatment strategies following at least one prior failed medication treatment attempt. Methods: In total, 1522 outpatients with MDD were randomized to switching to bupropion‐SR (S‐BUP), combining with bupropion‐SR (C‐BUP), or augmenting with aripiprazole (A‐ARI). Following 12 weeks of acute phase treatment, 725 entered the 24‐week continuation treatment phase. Depressive symptom severity, relapse, "emergent" remission, anxiety, suicidal ideation, quality of life, health status, and side effects were compared. Results: We did not find clinically significant differential treatment effects with the exception that A‐ARI was associated with less anxiety than S‐BUP or C‐BUP. Participants who entered continuation treatment as remitters had milder depressive symptom severity and lower relapse rates than those not in remission; they also experienced more improvement on most other outcomes. A‐ARI was associated with less anxiety, insomnia, and dry mouth but more somnolence, extrapyramidal effects, akathisia, abnormal laboratory values, and appetite and weight gain. Conclusions: Continuation treatment is a dynamic period. Regardless of the treatment, participants who entered continuation treatment at Week 12 in full remission continued to have better outcomes over the subsequent 24 weeks than those who were not in remission at the start of the continuation phase.